A mu-conotoxin-insensitive Na+ channel mutant: possible localization of a binding site at the outer vestibule. - Dudley, S C (1995)
We describe a mutation in the outer vestibule region of the adult rat skeletal muscle voltage-gated Na+ channel (microliter) that dramatically alters binding of mu-conotoxin GIIIA (mu-CTX). Mutating the glutamate at position 758 to glutamine (E758Q) decreased mu-CTX binding affinity by 48-fold. Because the mutant channel showed both low tetrodotoxin (TTX) and mu-CTX affinities, these results suggested that mu-CTX bound to the outer vestibule and implied that the TTX- and mu-CTX-binding sites partially overlapped in this region. The mutation decreased the association rate of the toxin with little effect on the dissociation rate, suggesting that Glu-758 could be involved in electrostatic guidance of mu-CTX to its binding site. We propose a mechanism for mu-CTX block of the Na+ channel based on the analogy with saxitoxin (STX) and TTX, on the requirement of mu-CTX to have an arginine in position 13 to occlude the channel, and on this experimental result suggesting that mu-CTX binds in the outer vestibule. In this model, the guanidinium group of Arg-13 of the toxin interacts with two carboxyls known to be important for selectivity (Asp-400 and Glu-755), with the association rate of the toxin increased by interaction with Glu-758 of the channel.